Effect of MDP concentration and addition of iodonium salt on the dentin bond strength of experimental adhesives - Kinder, Gustavo; Furuse, Adilson; Costa, Reginaldo; Lucena, Fernanda; Correr, Gisele; Gonzaga, Carla (Brazilian Dental Science, 2022)
Objective: The aim was to evaluate the bond strength of six experimental adhesives containing binary or ternary photoinitiator systems, associated with three different MDP concentrations (0-12wt%) after 12 months of storage in distilled water. Material and Methods: Experimental adhesives were prepared with: bis-GMA, UDMA, bis-EMA, TEGDMA, HEMA, BHT, and ethanol, containing binary (CQ/amine) or ternary (CQ/amine/DPIHFP (diphenyliodonium hexafluorophosphate) – 0.5wt%) photoinitiator systems. It was added to this composition 0wt%, 6wt%, or 12wt% of MDP. The adhesive systems were applied following the etch-and-rinse protocol. Transparent cylindrical molds were placed on the hybridized dentin, filled with composite resin and light-cured. The specimens were stored in distilled water at 37oC for 24h or 12 months and submitted to a microshear bond strength test (n=6). Data were analyzed by three-way ANOVA and Tukey’s test (a =5%). Results: For the binary system, after 12 months of storage, all bond strength values were similar. Regarding bond strength degradation over time, 6wt% and 12wt% MDP formulations showed more stable bond strength than 0wt% MDP. For the ternary system, all formulations (0wt%, 6wt% and 12wt%) showed stable bond strength over time. Conclusion: For the binary photoinitiator system, the 6wt% and 12wt% MDP concentrations were able to keep bond strength stable over time, while for the ternary system, bond strength stability was achieved regardless the MDP concentration. KEYWORDS Dental bonding; Dental photoinitiators; Dentin-bonding agents; MDP.